SIGNIFICANCE OF PARTIAL ROOT ZONE DRYING AND MULCHES FOR WATER SAVING AND WEED SUPPRESSION IN WHEAT - S. Ahmad; M. A. S. Raza; M. F. Saleem; R. Iqbal; M. S. Zaheer; I. Haider; M. U. Aslam; M. Ali; I. H. Khan (Journal of Animal and Plant Sciences, 2020)
One of the main negative effects of climate change is the increasing scarcity of water worldwide. Wheat is the second major staple food of the world and drought is the main factor affecting its production. In order to ensure food security, there is need to adopt easy and economic techniques for increasing crop production under limited water resources. Two of the effective techniques are; use of ground covers and partial root zone drying (PRD). Experiments were comprised of two irrigation methods (I1 = irrigation on both sides of roots and I2 = irrigation to only one side of root as alternate irrigation) and four ground covers (M0 = open ground without any cover, M1 = black plastic cover, M2 = wheat straw cover and M4 = cotton sticks cover). Results revealed that more spike length, number of spikelets and grains were found in full irrigation treatment. While water use efficiency and grain nutrient (NPK) contents were more in PRD. All soil covers suppress the weeds and significantly influenced the yield attributes as well as the grain nutrient contents. However, black plastic cover performed the best. It was concluded that joint use of both techniques was more effective than their sole application and combination of PRD with black plastic mulch performed the best than rest of the treatments.
Keywords: Ground covers; Partial root zone drying; grain yield; Quality traits; WUE; Weed control efficiency